2001
DOI: 10.1074/jbc.m006152200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD3 and Concanavalin A-induced Human T Cell Proliferation Is Associated with an Increased Rate of Arachidonate-Phospholipid Remodeling

Abstract: In this study arachidonate-phospholipid remodeling was investigated in resting and proliferating human T lymphocytes. Lymphocytes induced to proliferate with either the mitogen concanavalin A or with anti-CD3 (OKT3) in combination with interleukin 2 (OKT3/IL-2) showed a greatly accelerated rate of [ 3 H]arachidonatephospholipid remodeling compared with resting lymphocytes or with lymphocytes stimulated with OKT3 or IL-2 alone. The concanavalin A-stimulated cells showed a 2-fold increase in the specific activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…As noted above, some studies suggest that apoptosis is induced due to AA accumulation, a likely outcome of iPLA 2 activity [126][127][128]138]. There is evidence that iPLA 2 is involved in acyl chain remodeling and that apoptosis ensues when this process is inhibited [72,138]. However, as the role for iPLA 2 in acyl chain remodeling appears to be limited to macrophage cell lines [17,72,74,75], this is likely not a major mechanism for iPLA 2 -mediated apoptosis.…”
Section: Ipla 2 and Apoptosismentioning
confidence: 85%
See 2 more Smart Citations
“…As noted above, some studies suggest that apoptosis is induced due to AA accumulation, a likely outcome of iPLA 2 activity [126][127][128]138]. There is evidence that iPLA 2 is involved in acyl chain remodeling and that apoptosis ensues when this process is inhibited [72,138]. However, as the role for iPLA 2 in acyl chain remodeling appears to be limited to macrophage cell lines [17,72,74,75], this is likely not a major mechanism for iPLA 2 -mediated apoptosis.…”
Section: Ipla 2 and Apoptosismentioning
confidence: 85%
“…There is evidence that iPLA 2 is involved in acyl chain remodeling and that apoptosis ensues when this process is inhibited [72,138]. However, as the role for iPLA 2 in acyl chain remodeling appears to be limited to macrophage cell lines [17,72,74,75], this is likely not a major mechanism for iPLA 2 -mediated apoptosis. Other studies suggest that apoptosis downstream of AA accumulation is mediated through the generation of ceramide [139], a proapoptic sphingolipid derived from sphingomyelin hydrolysis [140].…”
Section: Ipla 2 and Apoptosismentioning
confidence: 92%
See 1 more Smart Citation
“…The iPLA 2 ␤, classified as a Group VIA isoform of iPLA 2 , is a member of a large family of PLA 2 s (27) that is cytosolic and does not require Ca 2ϩ for activity (28 -30). It is activated by ATP, is inhibited by the bromoenol lactone suicide substrate (BEL) inhibitor of iPLA 2 ␤ (31), and is recognized to have a role in signal transduction (28,(31)(32)(33)(34)(35)(36)(37)(38)(39). We found that induction of ER stress with the sarcoendoplasmic reticulum Ca 2ϩ -ATPase inhibitor thapsigargin causes INS-1 cell apoptosis that is amplified by overexpression of iPLA 2 ␤ and is inhibited by BEL (40).…”
Section: Our Recent Studies Indicate That Endoplasmic Reticulum (Er) mentioning
confidence: 92%
“…[5,6,8,9,11,12,14, H]AA (specific activity 211 Ci/mmol) and radioactive substrates for enzyme assays were from GE Healthcare. Thin layer chromatography plates were from Scharlab (Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%